The non-financial determinants of the financial derivatives’ usage within SME businesses in Pakistan - Nawaz, Muhammad; Mohd Harif, Mohd Amy Azhar; Azhari, Adilah Binti (Advances in Social Sciences Research Journal, 2018)
It had been recognized that the financial derivatives’ usage enhanced the financial performance of the firms despite larger and smaller firms. Many studies had been conducted on larger firms but very none of the studies had been conducted on financial derivatives’ usage within SMEs in the context of Pakistan. This space created thirst for the current research in exploring the non-financial determinants of the financial derivatives’ usage within SMEs in Pakistan. This research was aimed at pursuing the research problem: “how and why the non-financial determinants of the financial derivatives’ usage could be established within SMEs in Pakistan?” A qualitative research was conducted in order to investigate this research issue. Respondents of this research were identified by utilizing purposive snowballing sampling technique. Total nineteen (19) convergent interviews were conducted to establish the literature and to confirm the non-financial determinants of the financial derivatives’ usage within SMEs. Thematic analysis technique was used to analyze the data. The findings of this research confirmed twelve (12) non-financial determinants of the financial derivatives’ usage, i.e. growth opportunities, risk reduction, management incentives, corporate governance, risk attitude, risk perception, decision making unit, lack of awareness, lack of expertise, risk appetite, lack of established markets, time horizon. Three (3) newly discovered financial determinants of the financial derivatives’ usage were risk appetite, lack of established market and time horizon, which revealed the current research contribution to the existing literature. This research built a revised theoretical framework, which provided ground for future research.